A política de educação profissional articulada ao ensino médio na forma integrada no Paraná: uma análise da implementação no Colégio Estadual João Manoel Mondrone no município de Medianeira – Paraná (2003-2010) - Griebeler , Janice Rosangela Cardoso (2013)
In this study, we did an analysis of Professional Education policy articulated to high school in its integrated form in the state of Paraná and its implementation at Colégio Estadual João Manoel Mondrone, in Medianeira (PR), from 2003 to 2010. In this way, our analysis had by objective to investigate the process of implementation of Professional Education courses articulated to high school in its integrated form, with emphasis on propositions of politics and its possibility of effectiveness. The methodological course had qualitative and quantitative characteristics, contemplating the contextualization and the analysis of legal documents from Professional Education politics. We collected data at Secretaria Municipal de Educação of Medianeira (PR), Núcleo Reginal de Educação of Foz do Iguaçu (PR), Colégio Estadual João Manoel Mondrone and INEP and IPARDES websites. In the chapter A Reforma da Educação Básica e da Educação Profissional na Década de 1990, we sought to insert Professional Education in the dynamics of Brazilian educational policy, considering its historical determinants, in the sense of comprehending the context of Basic and Professional Education reformation from 1990, starting with Decree 2.208/1997 and 5.154/2004. In the chapter O Processo de Implantação da Educação Profissional na forma Integrada no Estado do Paraná, we did a study on polysemy existent around the terms about the relation between Professional Education and high school. We also presented the legal grounds which sustain the Professional Education reformation articulated to high school in its integrated form, as well as its application in the state of Paraná, at the time chosen for this study. In the chapter A implementação da Educação Profissional na forma Integrada no Colégio Estadual João Manoel Mondrone no Município de Medianeira - Paraná, we did the economic, social and educational characterization of Medianeira (PR) and the analisys of the implementation process of Professional Education articulated to high school in its integrated form to at Colégio Estadual João Manoel Mondrone. Among the results of this study, we highlight the significant advance of Professional Education policy articulated to high school in its integrated form in Paraná, from 2003 to 2010.